Labor Market and Distributional Effects of an Increase in the Retirement Age - Johannes Geyer; Peter Haan; Anna Hammerschmid; Michael Peters (Institute of Labor Economics (IZA), 2018)
We evaluate the labor market and distributional effects of an increase in the early retirement age (ERA) from 60 to 63 for women. We use a regression discontinuity design which exploits the immediate increase in the ERA between women born in 1951 and 1952. The analysis is based on the German micro census which includes about 370,000 households per year. We focus on heterogeneous labor market effects on the individual and on the household level and we study the distributional implications using net household income. In this respect we extend the previous literature which mainly studied employment effects on the individual level. Our results show sizable labor market effects which strongly differ by subgroups. We document larger employment effects for women who cannot rely on other income on the household level, e.g. women with a low income partner. The distributional analysis shows on average no significant effects on female or household income. This result holds as well for heterogeneous groups: Even for the most vulnerable groups, such as single women, women without higher education, or low partner income, we do not find significant reductions in income. One reason for this result is program substitution.
Keywords: J14; J18; J22; J26; H31; 330; retirement age; pension reform; labor supply; early retirement; distributional effects; spillover effects; household